Discovery and excavation of lichen bioactive natural products - Ren, Meirong; Jiang, Shuhua; Wang, Yanyan; Pan, Xinhua; Pan, Feng; Wei, Xinli (Frontiers in Microbiology, 2023)
Lichen natural products are a tremendous source of new bioactive chemical entities for drug discovery. The ability to survive in harsh conditions can be directly correlated with the production of some unique lichen metabolites. Despite the potential applications, these unique metabolites have been underutilized by pharmaceutical and agrochemical industries due to their slow growth, low biomass availability and technical challenges involved in their artificial cultivation. At the same time, DNA sequence data have revealed that the number of encoded biosynthetic gene clusters in lichen is much higher than natural products, and the majority of them are silent or poorly expressed. To meet these challenges, one strain many compounds (OSMAC) strategy, as a comprehensive and powerful tool, has been developed to stimulate the activation of silent or cryptic biosynthetic gene clusters and exploit interesting lichen compounds for industrial applications. Further, development of computational tools, network molecular techniques, modern bioinformatics and genetic tools are opening up a new opportunity for the mining, modification, and production of lichen metabolites, rather than merely using traditional separation and purification techniques to obtain small amounts of chemical compounds. The recent development of multiomics biodiscovery strategies aided by synthetic biology in order to study the heterologous expressed lichen-derived biosynthetic gene clusters in a cultivatable host offers a promising means for a sustainable supply of specialized metabolites. In this review, we summarized the bioactivity of lichen metabolites and highlighted application of OSMAC and genome mining-based strategy in lichen-forming fungi for discovery of new cryptic lichen compounds.